2014
DOI: 10.1017/s0144686x14000221
|View full text |Cite
|
Sign up to set email alerts
|

Home environments and adaptations in the context of ageing

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
0
24
0
3
Order By: Relevance
“…It has been suggested that individuals who do not think of HAs as useful do not apply for or make an HA [43]. Further, this study was a part of a larger longitudinal survey study on housing adaptations which restricted the sample of cohabitants.…”
Section: Methods Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that individuals who do not think of HAs as useful do not apply for or make an HA [43]. Further, this study was a part of a larger longitudinal survey study on housing adaptations which restricted the sample of cohabitants.…”
Section: Methods Discussionmentioning
confidence: 99%
“…Turning to methodological limitations, the cohabitants in this study were recruited based on their partners having applied for a housing adaptation, implying an overall positive attitude to HAs. It has been suggested that individuals who do not think of HAs as useful do not apply for or make an HA (41). Furthermore, this study was part of a larger longitudinal survey study on housing adaptations, which restricted the sample of cohabitants.…”
Section: Methods Discussionmentioning
confidence: 99%
“…Ageing in familiar surroundings has shown to have a positive correlation with health and well-being and sense of satisfaction and contentedness (Renaut, Ogg, Petite, & Chamahian, 2015;Hussein, Abidin, & Omar, 2016;Stones & Gullifer, 2016;Dahlan & SultanIbrahim, 2017;Yousefi, Hosseini, Yazdanfar, & Norouzian-Maleki, 2017). Older people wanting to remain in their homes and communities for as long as possible helps in the maintenance of social connection and support from family and friends (Lawler, 2001;Muhammad, 2016;Zakariya, Harun, & Mansor, 2016).…”
Section: Ageing-in-placementioning
confidence: 99%
“…Personalisation of space, use of design prompts, colours to 'theme' areas, meaningful artwork, pictorial signage and pictures can help orientate older people with dementia and other cognitive impairments. An environment that is designed to be intuitive and easy to use can enable older people to experience a sense of competence, choice and control, thus making a positive difference to a person's self-esteem (Faith, Hadjri, Rooney, Craig, & McAllister, 2015;Twyford, 2016;Walker, 2017).Ageing in familiar surroundings has shown to have a positive correlation with health and well-being and sense of satisfaction and contentedness (Renaut, Ogg, Petite, & Chamahian, 2015;Hussein, Abidin, & Omar, 2016;Stones & Gullifer, 2016;Dahlan & SultanIbrahim, 2017;Yousefi, Hosseini, Yazdanfar, & Norouzian-Maleki, 2017). Older people wanting to remain in their homes and communities for as long as possible helps in the maintenance of social connection and support from family and friends (Lawler, 2001;Muhammad, 2016;Zakariya, Harun, & Mansor, 2016).…”
mentioning
confidence: 99%
“…To achieve maximum independence for elderly adults, three things are essential (Heywood et al 2002): (1) the home needs to be in good conditions and not cause any physical or mental illness; (2) a service is available when required to help with housework; (3) adaptation is required that makes all the rooms accessible for older occupants. Within this context, housing adaptations are vital vehicles not only for moving to a broader choice of independent living arrangements (Fänge and Iwarsson 2005;Renaut et al 2015), but also for guaranteeing an effective usage of public resources (e.g. Chiatti and Iwarsson 2014;Heywood and Turner 2007;Howard-Wilsher et al 2016).…”
Section: Introductionmentioning
confidence: 99%